Caracterizações farmacológicas e bioquímicas de peçonhas de aranhas dos gêneros Lasiodora e Loxosceles - Carolina Campolina Rebello Horta (2012)
Spider venoms are complex mixtures of substances. Research into spider venoms investigates the mechanisms underlying envenomation, new therapeutic strategies and the huge pharmacological potential of the venom components. The present work studied the venoms of two distinct spiders: the Araneomorphae spider Loxosceles similis and the Mygalomorphae spider Lasiodora sp. In order to provide a better understanding of the study, this manuscript is divided into two chapters. CHAPTER 1 - Members of the spider genus Loxosceles can cause severe envenomation in humans, described as loxoscelism. Cutaneous loxoscelism is characterized by dermonecrosis which can require weeks to heal. Systemic loxoscelism is a rare complication marked by acute renal failure that leads to death in a few cases. Recently, the poorly studied L. similis species has been found in anthropic environments, mainly in the State of Minas Gerais. The first characterizations of the venom from this species showed that its main biological effects had a similar intensity to other medically important Loxosceles species. The aim of the first chapter of the present work was to characterize the specific anti-L. similis-venom serum and to evaluate the participation of LPA in the effects of both L. similis venom and L. intermedia dermonecrotic protein (recLiD1). Histological analysis of rabbit skin 2, 4 and 8 hours after intradermal injection of L. similis venom (3 µg) showed a dense inflammatory infiltrate, edema, muscle degeneration and necrosis, dissociation of collagen and reticular fibers. Pre-incubation of the venom with anti-L. similis-venom serum significantly decreased all of these effects. The main toxic component of Loxosceles spider venom presents phospholipase D (PLD) activity towards many lipid targets. There is current interest in investigating the role of lysophosphatidic acid (LPA) in loxoscelism. LPA is one of the products of PLD enzymatic action and it is described to induce platelet aggregation, endothelial hyperpermeability and pro-inflammatory responses. Treatment of HFF-1 human fibroblast cells with L. similis venom or recLiD1 (10 µg/mL, both pre-incubated with lysophosphatidylcholine, a precursor for LPA formation) provokes the release of pro-inflammatory cytokines and chemokines IL-6, IL-8, CXCL1, CXCL2 after 12 hours, as well as cell death by apoptosis after 48 hours of incubation. The concomitant treatment of the cells with Ki16425 (15 µM), an antagonist of LPA receptors (LPA1/LPA3), significantly decreased the production of inflammatory mediators; however, it did not reduce the apoptotic effects of venom and recLiD1. On HUVEC human endothelial cells, Ki16425 did not reduce apoptosis caused by venom and recLiD1 after 48 hours of incubation either. Thus the present work has showed for the first time that LPA formed by PLD-dependent enzymatic activity of L. similis venom and recLiD1 has an important role in the release of pro-inflammatory cytokines and chemokines from human fibroblasts. Nevertheless, LPA receptors do not participate in HFF-1 and HUVEC cell death caused by these agents, at least in vitro and under our experimental conditions. CHAPTER 2 - Members of the spider genus Lasiodora are widely distributed in Brazil, where they are commonly known as caranguejeiras. Lasiodora sp. spider venom is slightly toxic to humans. The bite of this spider causes local pain, edema and erythema. However, Lasiodora venom may be a source of important pharmacological tools. Our research group has previously described the cardiovascular effects of Lasiodora sp. venom. In rats, this venom produces acute hypotension and bradycardia, decreased heart rate in the isolated heart, nitric oxide (NO)-dependent vasodilation and activation of endothelial nitric oxide synthase enzyme (eNOS) in aortic rings. The aim of the second chapter of the present work was to isolate and characterize one or more vasodilator components from Lasiodora sp. crude venom. We isolated one vasoactive fraction using fractionation techniques combined with biological assays in rat aorta. Mass spectrometry and nuclear magnetic resonance assays identified that the fraction is a mixture of two compounds: adenosine diphosphate (ADP, 88%) and adenosine monophosphate (AMP, 12%). It is known that ADP, as well as the crude venom, causes hypotension, NO-dependent vasodilation and eNOS activation. We determined that Lasiodora sp. venom contains enough amount of ADP to cause relaxation in rat aortic rings. The vasodilator effects of ADP and Lasiodora crude venom were significantly inhibited by suramin, which is a P2-purinergic receptors antagonist. The results of the present work indicate that ADP is an important vasodilator component of Lasiodora sp. spider venom.